1979
DOI: 10.1038/bjc.1979.216
|View full text |Cite
|
Sign up to set email alerts
|

A new theory of carcinogenesis

Abstract: Summary.-Although many carcinogens are mutagens, there is no direct evidence that the cancer-cell phenotype is the result of gene mutation. Transplantation experiments have strongly indicated that malignant cells can arise or revert to the normal phenotype in the absence of mutation. It is suggested that damage to DNA followed by repair triggers the epigenetic changes in gene expression which are responsible for malignancy. We previously proposed that methylation of specific DNA sequences adjacent to structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
2

Year Published

1981
1981
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(59 citation statements)
references
References 44 publications
(35 reference statements)
2
55
0
2
Order By: Relevance
“…The effects of 5-azaC on the proliferative features of the three lines suggest that changes in methylation patterns have a central role in the generation of biological diversity. Such diversity may on the other hand be a necessary feature of malignant behavior (26, 32) as well as it is conceivable that demethylation is an important event in oncogenesis (33). It was also recently demonstrated that demethylation of certain genes in the murine Lewis lung tumor system may lead to metastatic activity of otherwise nonmetastatic cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of 5-azaC on the proliferative features of the three lines suggest that changes in methylation patterns have a central role in the generation of biological diversity. Such diversity may on the other hand be a necessary feature of malignant behavior (26, 32) as well as it is conceivable that demethylation is an important event in oncogenesis (33). It was also recently demonstrated that demethylation of certain genes in the murine Lewis lung tumor system may lead to metastatic activity of otherwise nonmetastatic cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that hypomethylation of DNA may provide a common transforming mechanism shared by chemical carciidogens and oncogenic viruses. Genetic vs. epigenetic considerations A purely epigenetic model of carcinogenesis, also concerned with the effects of hypomethylation upon cell populations, has been put forward (Holliday, 1979). This model proposes that damage to DNA results in the potentially reversible loss of methyl groups as a function of repair processes.…”
Section: -Mc Depletion During Tumour Developmentmentioning
confidence: 99%
“…In the case of a genetic programme, the explanation is easy: Mutation, or an epigenetic change in gene regulation (Holliday 1979), may simply interrupt the programme. Most carcinogens are, after all, potent mutagens.…”
Section: "Immortalisation" Of Transformed Cellsmentioning
confidence: 99%